A Common Origin for Immunity and Digestion - Broderick, Nichole A. (Frontiers in Immunology, 2015)
Historically the digestive and immune systems were viewed and studied as separate entities. However, there are remarkable similarities and shared functions in both nutrient acquisition and host defense. Here, I propose a common origin for both systems. This association provides a new prism for viewing the emergence and evolution of host defense mechanisms.